A marine to fluvial transition in the the Paleoproterozoic Koolbye Formation, Turee Creek Group, Western Australia. - Mazumder, Rajat; Van Kranendonk, M.; Altermann, W. (Elsevier BV, 2015)
Although no unambiguous biogenic criteria exist to discriminate Precambrian shallow-marine successions from fluvial deposits, physical sedimentological evidence, including an association of primary sedimentary structures and textures, stratigraphic position, and comparison with Phanerozoic and Modern examples has been found useful in identifying these deposit types. Our high resolution sedimentary facies analysis coupled with new mapping clearly indicates shallow-marine to beach-aeolian to fluvial sedimentation in the Paleoproterozoic Koolbye Formation of the Turee Creek Group, Western Australia. A falling stage systems tract within the Koolbye Formation has been documented. Our sedimentary facies analysis in combination with sedimentological analysis of the underlying Kungarra Formation indicates development of at least three falling stage systems tracts within the Turee Creek Group across the rise of atmospheric oxygen (the Great oxidation event).